Genetic Resource of Muscovy Duck (Cairina moschata): Profile and Potential Production as Meat Producer - Hasil Tamsil (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2018)
Muscovy duck is a type of waterfowl that has a relatively better growth and percentage compared to ducks. Duck meat has high-quality because of its low fat and savory flavor. Muscovy duck is relatively resistant to the disease and is able to use low-quality feed, but has the disadvantage of low egg production. The development of Muscovy duck as a producer of meat can be done through two approaches, namely the long-term and short-term. The long-term approach is carried out by selecting Muscovy duck which has high growth rate and high meet quality. The selection can be done in two ways, namely directly on the nature of growth and the quality of meat, and indirectly by choosing a marker of growth (morphology, biochemistry or diversity of DNA/ RNA). Short-term selection can be done by bringing in superior Muscovy duck from the outside to be developed by farmers and crossing male Muscovy duck with the layer Indian Runner ducks to produce Serati ducks.